Enhancing operational efficiency in plastic manufacturing SMES through lean manufacturing and TPM: a case study - Navarro Bendezu, Jampier Anderson (2025)
This research proposes a comprehensive model that combines Lean Manufacturing and Total Productive Maintenance (TPM) methodologies in a company dedicated to marketing products that use recycled plastic as raw material. The model includes the implementation of 5S to organize the workplace, autonomous maintenance to train operators in routine maintenance tasks, and planned maintenance to enhance communication and efficiency. The implementation of the model resulted in significant improvements: the reprocessing rate for burning in the extruder decreased from 2.20% to 1.36%, Overall Equipment Efficiency (OEE) increased from 57.69% to 85.10%, the Mean Time to Repair (MTTR) was reduced from 5.31 hours to 2.69 hours, and downtime decreased from 9.45 minutes to 5.15 minutes. These results demonstrate the effectiveness of the model in improving production efficiency and reliability, leading to cost savings and increased competitiveness for the company.